HUBUNGAN UMUR BALITA DAN STATUS IMUNISASI DENGAN KEJADIAN INFLUENZA PADA BALITA DI PUSKESMAS BASUKI RAHMAT PALEMBANG TAHUN 2011 - Wahyu Ida, Khodijah Wahyu Ida, Khodijah (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2012)
ABSTRACT Influenza is a viral infection of the mucous membranes, nose, sinuses and respiratory tract large. Under-five mortality rate (IMR) in South Sumatra is higher than the national figure of 42 per 1000 live births. The purpose of this study is to determine hubungann toddler age and immunization status with the incidence of influenza in health center Basuki Rahmat Palembang in 2011, this study used survey methods of analytic approach "Cross Sectional". The population in this study were all mothers who bring young children with influenza symptoms seeking treatment at health centers Basuki Rahmat Palembang, sampling conducted in non-random techniques "Accidental Sampling" can be as many as 30 respondents. The research was conducted on 13 June to 24 June 2011. From the analysis of data showed the respondents who experienced influenza at (53.3%) while respondents are not influenza at (46.7%). Respondents who are at high risk for age (66.7%) and low-risk age (33.3%) and respondents with incomplete immunization status sebesr (56.7%) while those for incomplete immunization status (43.3%). From the results of Chi-Square test found no significant relationship between age of a toddler with the incidence of influenza in which the p value (0.001) and no significant relationship between the incidence of influenza immunization status where p Value = 0.001. Based on the results of the study researchers recommend to improve its performance in conducting health services and in an effort to reduce the incidence of influenza in infants. ABSTRAK Influenza merupakan suatu infeksi virus pada selaput lendir, hidung, sinus dan saluran nafas besar. Angka kematian balita (AKB) di Sumsel lebih tinggi dibandingkan Angka Nasional yaitu 42 per 1000 kelahiran hidup. Tujuan penelitian ini yaitu untuk mengetahui hubungann umur balita dan status imunisasi dengan kejadian influenza di Puskesmas Basuki Rahmat Palembang Tahun 2011, penelitian ini menggunakan metode survei analitik dengan pendekatan ”Cross Sectional”. Populasi dalam penelitian ini adalah semua ibu yang membawa balita dengan gejala influenza yang berobat di Puskesmas Basuki Rahmat Palembang, pengambilan sampel dilakukan secara non random dengan teknik ” Accidental Sampling” didapatkan sebanyak 30 responden. Penelitian ini dilakukan pada tanggal 13 Juni – 24 Juni Tahun 2011. Dari hasil analisa data menunjukkan responden yang mengalami influenza sebesar (53,3%) sedangkan responden yang tidak influenza sebesar (46,7%). Responden umur yang beresiko tinggi sebesar (66,7%) dan umur yang resiko rendah (33,3%) dan responden dengan status imunisasi lengkap sebesr (56,7%) sedangkan yang status imunisasi tidak lengkap sebesar (43,3%). Dari hasil uji Chi-Square didapatkan ada hubungan bermakna antara umur balita dengan kejadian influenza dimana p value (0,001) dan ada hubungan bermakna antara status imunisasi dengan kejadian influenza dimana p Value = 0,001. Berdasarkan hasil penelitian peneliti menyarankan untuk meningkatkan kinerjanya dalam melakukan pelayanan kesehatan serta dalam upaya menurunkan angka kejadian influenza pada balita.